1980
DOI: 10.1111/j.1570-7458.1980.tb02969.x
|View full text |Cite
|
Sign up to set email alerts
|

OVIPOSITION RESPONSE OF PIERIS RAPAE TO ENVIRONMENTALLY INDUCED VARIATION IN BRASSICA NIGRA

Abstract: Oviposition preferences of field collected Pieris rapae (L.) adults were tested on Brassica nigra (Koch) plants which had been grown under four nutrient treatments. Each oviposition trial tested the preference between two treatments. In some oviposition preference tests females demonstrated a clear preference for one treatment, but in other trials, no preferences were observed. Leaf water content was implicated as a phenotypic characteristic associated with oviposition preference. Demonstrated oviposition pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 23 publications
2
56
1
Order By: Relevance
“…For example, Dentaria diphylla was heavily damaged by insects when transplanted from forest to old field (Hicks and Tahvanainan 1974). Brassica nigra grown in the laboratory with lower soil water availabilities was preferentially used by Pieris rapae (Wolfson 1980(Wolfson , 1982. And, in our study system, greater insect damage occurs on bittercress plants: ( (Louda 1986); and (4) on chemically stressed treatments (Louda 1988).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…For example, Dentaria diphylla was heavily damaged by insects when transplanted from forest to old field (Hicks and Tahvanainan 1974). Brassica nigra grown in the laboratory with lower soil water availabilities was preferentially used by Pieris rapae (Wolfson 1980(Wolfson , 1982. And, in our study system, greater insect damage occurs on bittercress plants: ( (Louda 1986); and (4) on chemically stressed treatments (Louda 1988).…”
mentioning
confidence: 73%
“…In contrast to the laboratory results (Wolfson 1982), oviposition and feeding by Pieris rapae were not greater on cabbages that were grown in pots at lower water availabilities (Miles et al 1982b, Myers 1985. The next obvious step, which we take here, is to experimentally evaluate both the response of the plant and of the insect herbivores to the imposition of moderate stress under natural field conditions.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In another study from the 1980s regarding oviposition preferences of field-collected P. rapae butterflies towards B. nigra plants, leaf water content was considered as a phenotypic characteristic associated with oviposition preference (Wolfson, 1980). Renwick and Radke (1985) further showed that oviposition by P. rapae on cabbage was deterred by homogenised cabbage tissue sprayed onto intact plants.…”
Section: White Butterflies (Pieris Brassicae and P Rapae)mentioning
confidence: 99%
“…Selective pressures should result in females ovipositing in leaves which promote increased larval development and survival (Mitchell 1975, Wiren & Larsson 1984, Larsson et al 1986; but see Chew 1977, Wolfson 1982. Therefore, larval occurrence and damage should reflect qualitative and quantitative differences in plant quality detectable by the ovipositing female (Chew 1977, Rausher 1979.…”
Section: Ipm Project 1985)mentioning
confidence: 99%